The Woman in the Poetry of fadl Mukhadar: Diwan (Sulat Turab)- A Model - Al-Saede, Najah Jasim Meala (Al-Adab Journal, 2020)
Woman represent the inspiration source, the birthplace of tenderness, and the energy of life continuity and renewal. If art is a color of the social life expression colors in all of its dimensions, then poetry is one of the oldest arts that Arabs knew, woman had a distinctive presence in the poets production, for woman left her marks on the pages of the poets feelings, and infused within his depths, merged in the colors of his mental state, so she had an active impact in drafting his personal experiences.The extent of woman’s presence on a vast space of the poetry production comes from the authenticity of the woman’s human existence, and by the multiple roles that she performs in life as a mother, wife, lover, daughter and sister.Woman has recorded a distinctive presence in the poetry of Sheikh Fadil Mukhaddir. She achieved an apparent domination over many of the poems that the woman was its main theme, and the central idea from which a range of ideas and pulsing images in the heart of the text.In this research, I will try to observe the woman imagery in the (a connection of soil) collection of poetry by Fadil Mukhaddir, to follow through with her appearance in every script of the text, and to identify the nature of that appearance and know it’s beautiful and semantic impact on producing these creative texts.The nature of the research demanded that it consists of an introduction, a preface specific for shedding light on the concept of (woman), and an introduction of the poet (Fadil Mukhaddir)in short. Afterwards, presenting the poetic texts and analyzing them according to the mechanisms of the analytic descriptive methodology, finally the conclusion brings out the most important results of the research, followed by the references list.